Community policing, social capital, and residents' feelings of safety in Taiwan. (2nd January 2023) - Lo, Tzu-Ying; Wolff, Kevin T.; Liu, Yu-Hsuan; Tsai, Hui-Er
ABSTRACT: The history of community policing has now reached a half-century mark, but evidence regarding its effectiveness in reducing fear of crime has been inconsistent. A closer examination of existing research suggests that there must be an underlying process linking community policing and community residents' fear of crime. Thus, this study draws on Putnam's theoretical framework to test a conceptual mechanism of social capital underlying the association between elements of community policing and residents' feelings of safety. Using survey data from a sample of Taiwanese residents, this study applies structural equation modeling to assess the potential mediating effect of social capital. The results suggest community policing is positively associated with residents' social capital, residents' social capital is positively associated with their feelings of safety, and community policing has a significant indirect effect on residents' feelings of safety through residents' social capital. Based on the findings of this study, suggestions for future research and criminal justice policy are provided.